Organic–Inorganic Hybrid Cuprous‐Based Metal Halides for Warm White Light‐Emitting Diodes - Meng, Xuan; Ji, Sujun; Wang, Qiujie; Wang, Xiaochen; Bai, Tianxin; Zhang, Ruiling; Yang, Bin; Li, Yimeng; Shao, Zhipeng; Jiang, Junke; Han, Ke‐li; Liu, Feng (Advanced science, 2022)
Single‐component emitters with stable and bright warm white‐light emission are highly desirable for high‐efficacy warm white light‐emitting diodes (warm‐WLEDs), however, materials with such luminescence properties are extremely rare. Lowdimensional lead (Pb) halide perovskites can achieve warm white photoluminescence (PL), yet they suffer from low stability and PL quantum yield (PLQY). While Pb‐free air‐stable perovskites such as Cs2AgInCl6 emit desirable warm white light, sophisticated doping strategies are typically required to increase their PL intensity. Moreover, the use of rare metal‐bearing compounds along with the typically required vacuum‐based thin‐film processing may greatly increase their production cost. Herein, organic–inorganic hybrid cuprous (Cu+)‐based metal halide MA2CuCl3 (MA = CH3NH3+) that meets the requirements of i) nontoxicity, ii) high PLQY, and iii) dopant‐free is presented. Both single crystals and thin films of MA2CuCl3 can be facilely prepared by a low‐cost solution method, which demonstrate bright warm white‐light emission with intrinsically high PLQYs of 90–97%. Prototype electroluminescence devices and down‐conversion LEDs are fabricated with MA2CuCl3 thin films and single crystals, respectively, which show bright luminescence with decent efficiencies and operational stability. These findings suggest that MA2CuCl3 has a great potential for the single‐component indoor lighting and display applications. The newly developed hybrid MA2CuCl3 meets the requirements of i) broadband warm white‐light emission, ii) nontoxicity, iii) high photoluminescence quantum yield, iv) dopant‐free, v) low‐cost, and vi) excellent film‐forming ability. Besides, the first successful electroluminescence application of MA2CuCl3 opens a new avenue toward single‐component warm white light‐emitting diodes.